IMPLEMENTASI PERATURAN WALIKOTA NOMOR 16 TAHUN 2009 TENTANG PENATAAN DAN PEDOMAN MENARA TELEKOMUNIKASI BERSAMA DI KOTA PEKANBARU - Andi Linda Purmasari; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose in this research was how the implementation of PERWAKO No.16 in 2009 and what factors that influenced those implementation.The theory conceptused by researcher was public policy and policy implementation. In addition, thisresearch used qualitative methodology with descriptively data study. In collecting thedata, the researcher used interview technique and observation, and by using keyinformant as the source of information.The result of this research showed thatimplementation of PERWAKO no. 16 in 2009 regarding arrangement and orientationof sharing telecommunication towers in Pekanbaru city has not completely workedyet, because based on the influencing factor, there still many owners or providers ofthe tower who develop the tower for their own provider needs, not considering theenvironment around the tower, and never involving the nearest society in the tower.Key words:ImplementationPolicy,PERWAKO, Telecommunication Tower